1993
DOI: 10.1093/clinchem/39.10.2040
|View full text |Cite
|
Sign up to set email alerts
|

Urinary selenium concentrations

Abstract: Urinary selenium concentrations are used as an indicator of selenium status. A strong correlation has been established between dietary selenium and daily urinary selenium excretion in a wide range of populations from all over the world with different dietary selenium intake. Data on urinary selenium concentrations in healthy individuals and patients with different pathological conditions are reviewed. Selenium excretion rates of 20-200 micrograms/day are not associated with deficiency or toxicity problems. Uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 28 publications
1
55
2
Order By: Relevance
“…[6][7][8][9] In contrast, the urinary selenium concentration was in the reference range; yet because of polyuria, daily loss of selenium was greater than that reported for healthy adults. 10 For manganese and nickel, the urine concentration and daily excretion exceeded that of reference populations. [11][12][13]…”
Section: Urine Concentration and Loss Of Trace Elements After Traumatmentioning
confidence: 96%
See 1 more Smart Citation
“…[6][7][8][9] In contrast, the urinary selenium concentration was in the reference range; yet because of polyuria, daily loss of selenium was greater than that reported for healthy adults. 10 For manganese and nickel, the urine concentration and daily excretion exceeded that of reference populations. [11][12][13]…”
Section: Urine Concentration and Loss Of Trace Elements After Traumatmentioning
confidence: 96%
“…POLY patients lost more total selenium than reference amounts of 30-75 µg/d. 10,36,37 The loss by trauma patients also exceeded the 60 µg/d amount in PN (averaging 173% of the amount in PN). These results reinforce findings by Berger et al 38 that urinary selenium losses are increased above normal during selenium supplementation after severe traumatic injury, although we report substantially greater losses of selenium.…”
Section: Seleniummentioning
confidence: 96%
“…By reviewing data on urinary selenium from various populations, Sanz Alaejos and Diaz Romero (1993) reported a strong correlation between dietary selenium and daily urinary selenium excretion over a wide range of dietary selenium intake (r = 0.962, p < 0.001; log-log relationship). Linear equations between 24-hour urinary selenium excretion and selenium intake have been published by these authors (log-log relationships) (Yang et al, 1989b;Sanz Alaejos and Diaz Romero, 1993;Longnecker et al, 1996). However, in addition to the amount of selenium ingested, various factors influence 24-hour urinary selenium excretion, including the chemical nature of dietary selenium (Burk et al, 2006), the composition of the diet, baseline selenium status and kidney function (Oster and Prellwitz, 1990).…”
Section: Urinary Selenium Excretionmentioning
confidence: 99%
“…It has been shown that the amount of Se in the kidney, calculated per wet mass, is 1.4 to about 3 times higher than in the liver and 6.6 to 10 times higher than in skeletal muscles (Zachara et al, 2001b). The Se level in tissues/organs depends on its daily intake, the chemical form of ingested Se and probably on other unknown factors (Lockitch, 1989;Alaejos & Romero, 1993). Thus the tissue Se level in people from seleniferous regions is much higher than in those living in low Se areas (Zachara et al, 2001b).…”
Section: Selenium In Blood Components and Se Metabolites In Urine Of mentioning
confidence: 99%
“…The predominant route of Se excretion in the healthy human is urine and feces (Robberecht & Deelstra, 1984;Alaejos & Romero, 1993). Se losses in urine represent 50-70% of the ingested element.…”
Section: Selenium In Blood Components and Se Metabolites In Urine Of mentioning
confidence: 99%